Welcome to Westonci.ca, where curiosity meets expertise. Ask any question and receive fast, accurate answers from our knowledgeable community. Get detailed and accurate answers to your questions from a dedicated community of experts on our Q&A platform. Discover in-depth answers to your questions from a wide network of professionals on our user-friendly Q&A platform.
Sagot :
To find the fourth term of a geometric sequence, we need to use the formula for the nth term of a geometric sequence. The formula is:
[tex]\[ a_n = a_1 \cdot r^{(n-1)} \][/tex]
where:
- [tex]\( a_n \)[/tex] is the nth term
- [tex]\( a_1 \)[/tex] is the first term of the sequence
- [tex]\( r \)[/tex] is the common ratio
- [tex]\( n \)[/tex] is the term number we want to find
Given:
- The first term ([tex]\( a_1 \)[/tex]) is 7
- The common ratio ([tex]\( r \)[/tex]) is -4
- We want to find the fourth term ([tex]\( a_4 \)[/tex])
Substitute these values into the formula:
[tex]\[ a_4 = 7 \cdot (-4)^{(4-1)} \][/tex]
[tex]\[ a_4 = 7 \cdot (-4)^3 \][/tex]
Now, calculate [tex]\( (-4)^3 \)[/tex]:
[tex]\[ (-4)^3 = (-4) \cdot (-4) \cdot (-4) \][/tex]
[tex]\[ (-4) \cdot (-4) = 16 \][/tex]
[tex]\[ 16 \cdot (-4) = -64 \][/tex]
So,
[tex]\[ (-4)^3 = -64 \][/tex]
Next, multiply this result by the first term:
[tex]\[ a_4 = 7 \cdot (-64) \][/tex]
[tex]\[ a_4 = -448 \][/tex]
Thus, the fourth term of the geometric sequence is:
[tex]\[ a_4 = -448 \][/tex]
[tex]\[ a_n = a_1 \cdot r^{(n-1)} \][/tex]
where:
- [tex]\( a_n \)[/tex] is the nth term
- [tex]\( a_1 \)[/tex] is the first term of the sequence
- [tex]\( r \)[/tex] is the common ratio
- [tex]\( n \)[/tex] is the term number we want to find
Given:
- The first term ([tex]\( a_1 \)[/tex]) is 7
- The common ratio ([tex]\( r \)[/tex]) is -4
- We want to find the fourth term ([tex]\( a_4 \)[/tex])
Substitute these values into the formula:
[tex]\[ a_4 = 7 \cdot (-4)^{(4-1)} \][/tex]
[tex]\[ a_4 = 7 \cdot (-4)^3 \][/tex]
Now, calculate [tex]\( (-4)^3 \)[/tex]:
[tex]\[ (-4)^3 = (-4) \cdot (-4) \cdot (-4) \][/tex]
[tex]\[ (-4) \cdot (-4) = 16 \][/tex]
[tex]\[ 16 \cdot (-4) = -64 \][/tex]
So,
[tex]\[ (-4)^3 = -64 \][/tex]
Next, multiply this result by the first term:
[tex]\[ a_4 = 7 \cdot (-64) \][/tex]
[tex]\[ a_4 = -448 \][/tex]
Thus, the fourth term of the geometric sequence is:
[tex]\[ a_4 = -448 \][/tex]
Thanks for stopping by. We are committed to providing the best answers for all your questions. See you again soon. Thank you for your visit. We're dedicated to helping you find the information you need, whenever you need it. We're here to help at Westonci.ca. Keep visiting for the best answers to your questions.